SOSIALISASI LITERASI FINTECH MELALUI HARMONISASI PERAN BANK INDONESIA DALAM MENDUKUNG KEBERLANJUTAN BISNIS UMKM DI ERA SOCIETY 5.0 - Sita Deliyana Firmialy; Akhmad Yunani; I Nyoman Bontot; Budi Rustandi Kartawinata (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The rapid development of financial technology (fintech) in the era of Society 5.0 presents both opportunities and challenges for Micro, Small, and Medium Enterprises (MSMEs) in achieving business sustainability. Although the adoption of digital financial services continues to increase, the level of fintech literacy among MSMEs remains relatively low, potentially leading to risks in financial management and business decision-making. This community service program aims to enhance fintech literacy through the harmonization of the roles of Bank Indonesia with academics, industry partners, and community stakeholders in supporting MSME business sustainability. The program employed a participatory applied research approach using a hybrid method that combined offline and online activities. The activities included needs assessment, fintech literacy socialization, lectures, and participatory discussions involving representatives from Bank Indonesia, MSME actors, academics, students, and other relevant stakeholders. The results indicate an improvement in participants’ understanding of fintech concepts, the benefits and risks of digital financial services, and the importance of responsible and sustainable fintech utilization. The harmonization of roles among stakeholders proved effective in strengthening educational outcomes and increasing MSMEs’ awareness of prudent digital financial practices. This program is expected to serve as an initial collaborative model for strengthening fintech literacy to support sustainable business development in the Society 5.0 era.